2018
DOI: 10.1007/s10552-018-1040-1
|View full text |Cite
|
Sign up to set email alerts
|

Intake of dietary carbohydrates in early adulthood and adolescence and breast density among young women

Abstract: Insulinemic carbohydrate diet during puberty may be associated with adulthood breast density, but our findings need replication in larger studies. Clinical Trials Registration ClinicalTrials.gov Identifier, NCT00458588 April 9, 2007; NCT00000459 October 27, 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
(110 reference statements)
1
4
0
Order By: Relevance
“…As previously noted PBW is strongly correlated with mammographic density 30 , a strong risk factor for breast cancer in adult women 29 . Previous studies have also shown that breast water is principally associated with the breast bro-glandular tissue that is observed as radiologically dense 31 .…”
Section: Discussionsupporting
confidence: 56%
“…As previously noted PBW is strongly correlated with mammographic density 30 , a strong risk factor for breast cancer in adult women 29 . Previous studies have also shown that breast water is principally associated with the breast bro-glandular tissue that is observed as radiologically dense 31 .…”
Section: Discussionsupporting
confidence: 56%
“…Numerous epidemiologic studies have shown an association between sugar and breast cancer ( Table 1 ) [ 46 , 47 ]. Additionally, sucrose intake during adolescence [ 48 ] was significantly correlated with higher percentage of dense breast volume [ 49 ], a known risk factor for breast cancer [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The current review revealed evidence linking added sugar consumption to increased cancer incidence and mortality. The epidemiologic evidence was strongest for breast cancer [ 49 , 51 , 53 ], and we also identified studies examining and finding a connection between added sugar and colon cancer [ 11 , 55 ]. Research on the association between added sugar consumption and pancreatic cancer was mixed [ 12 , 13 , 57 , 58 , 59 ], yet the preponderance of the evidence suggests an association.…”
Section: Discussionmentioning
confidence: 99%
“…We lacked the ability to distinguish between sugars such as sucrose or fructose that may have differential impacts on body development. For instance, a United States-based study found that adolescent sucrose intake, but not fructose, was positively associated with dense breast volume in early adulthood [ 60 ]. Sucrose, a common table sugar, is also associated with increased BMI among adults [ 61 ].…”
Section: Discussionmentioning
confidence: 99%